Исследование проблемы развития толерантного взаимодействия студентов педагогического вуза - Жаркунгулова, З.Д. (My University, 2013)
The degree of development of modern science pedagogical institute students` tolerant interaction is defined in this article. The results of diagnostics of the students` level of tolerance is given, the analysis of which shows that the system of preparation of future teachers isn`t enough dedicated to the development of tolerant interaction.